In Situ Observation of the Degradation Behavior and the Systematic Investigation of Corrosion Mechanism in AZ31 Alloy. Issue 10 (13th May 2021) - Yan, Xudong; Chen, Lanyue; Xu, Xiaofeng; Zhao, Yuguang; Zhao, Mingchun
Abstract : The degradation behaviors of as‐received and as‐solutionized AZ31 alloys in Hanks' solution are in situ studied by a 3D digital optical microscope. The initiation and extension processes of corrosion are investigated. Long‐time immersion and electrochemical tests are applied to investigate the corrosion mechanism systematically. The corrosion attacks of as‐received and as‐solutionized AZ31 alloy both start from the grain boundaries (with and without the Al8 Mn5 phase) while show no preferential propagation, and the scratches also can act as the corrosion starting positions. The Al8 Mn5 phase does not show an obvious accelerated effect on the Mg matrix's corrosion, and it also suffers corrosion. Solid solution treatment can enhance the corrosion resistance of AZ31 alloy is primarily due to the reduced dislocation density. Degradation products on as‐received AZ31 alloy are studied, the Al, Zn, and Mn elements degrade as Al2 O3, ZnO, and MnO, respectively. Abstract : The degradation behaviors of as‐received and as‐solutionized AZ31 alloys in Hanks' solution are investigated in situ by a 3D digital optical microscope. The grain boundary and scratch both act as corrosion starting positions; however, the propagation of corrosion indicates no particularly preferential. As‐solutionized AZ31 alloy shows better corrosion resistance due to containing less dislocation.